Digitalisasi Tabungan Siswa Online Transaction Gateway Menggunakan Midtrans Berbasis Android - Siti Sufaidah; Muhammad Ferdiansya; Moh. Anshori Aris Widya (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to develop an Android-based application utilizing an Online Transaction Gateway (OTG) for a student savings system. The application is designed as a solution to the manual system that requires parents to deposit savings directly at school and record transactions in a physical savings book. With this application, parents can deposit money through bank transfers or convenience stores without the need to visit the school.The application enables automatic bill generation and offers flexible payment options. Transaction history can be viewed in real time, and savings records can be printed or saved as digital files. With these features, parents can easily and transparently monitor their child’s savings.